(untitled) (Bioagro, 2020)
Viral diseases are one of the most important limiting factors of the production of tomato. In the world about 136 viral species have been reported to infect this plant but only 15 have been registered in Colombia, thus far. The latter suggests that the tomato virome in Colombia is underrepresented. In this work, the diversity of RNA viruses infecting tomato var. Chonto crops in eastern Antioquia was evaluated by RT-PCR, RT-qPCR, Next-generation sequencing (NGS) and Sanger sequencing. NGS revealed the presence of Potato virus Y (PVY), Potato yellow vein virus (PYVV), Potato virus S (PVS) and Potato virus X (PVX). PVX (6428 nt) and PVS (8492 nt) were the most abundant viruses and were completely assembled using the RNA-seq data. Infection by all four viruses was confirmed by RT-qPCR and Sanger sequencing of RT-PCR amplicons. These results highlight the need to strengthen the integrated disease management program for tomato in Colombia. This work is the first formal report of PVS and PVX naturally infecting tomato in Colombia.